Reduction of Chromium Evaporation with Manganese-based Coatings - Trebbels, Rene; Markus, Torsten; Singheiser, Lorenz (ECS transactions, 2009)
The vaporization of Cr-rich volatile species from interconnector materials for high temperature SOFC`s is considered to be a major source of degradation that limits the lifetime of planar SOFC systems [1-6]. For a longer lifetime of these systems, the Cr vaporization of interconnector material shall be reduced [7]. The potential of reduction of the Cr vaporization using coatings with spinel layers is the subject of the present work. In this study the Crofer22APU, IT-11 and F17 TNB interconnector steel is coated with Mn3O4 and (Mn,Co,Fe)3O4 powder as protective layer and LCC10 and LCC13 as contact layer. The coatings were done with wet powder spraying technique (wps) and atmospheric plasma spraying technique (aps). The Cr vaporization rates were studied at 800degree signC in air using the transpiration method. The measured Cr release of the coated samples was compared to uncoated samples. By using Mn3O4 the Cr vaporization rate was found to be 1 order of magnitude lower than uncoated steel. By using (Mn,Co,Fe)3O4 the Cr vaporization rate was found to be 2 orders of magnitude lower than uncoated steel. The Cr-evaporation is depended on the coating technique